Three new species of Ligophorus Euzet & Suriano, 1977 (Monogenea: Ancyrocephalidae) from Moolgarda buchanani (Bleeker) off Johor, Malaysia based on morphological, morphometric and molecular data - Soo, O.Y.M.; Tan, W.B.; Lim, L.H.S. (National University of Singapore, 2015)
Ligophorus liewi, new species, L. johorensis, new species, and L. grandis, new species, are described from Moolgarda buchanani off Johor, Malaysia. Ligophorus liewi, new species, is similar to L. kederai in having fenestrated ventral anchors but differs in having a distally tapered and bent accessory piece of the copulatory organ. Ligophorus johorensis, new species, is similar to L. kedahensis but it differs in having a raised antero-median protuberance (AMP) and longer copulatory tube. Ligophorus grandis, new species, is the largest Malaysian Ligophorus species and can be differentiated from the other species by its distally hooked-shaped accessory piece. Principal Component Analysis (PCA) scatterplot indicates that these three new species can be differentiated from each other and 10 described Malaysian Ligophorus species based on the morphometries of their sclerotised hard parts. Numerical taxonomy (NT) analysis indicates that the three new species are 38% similar to each other and the other 59 described Ligophorus species with differences primarily observed in size and shape of anchors, bars and male copulatory organs. Partial 28S rDNA and complete ITS1 from the three new and 10 previously described Malaysian Ligophorus species were sequenced. Maximum parsimony (MP) analysis based on these molecular data recovered a monophyletic clade that includes the three new species, and three previously described species, L. kedahensis, L. fenestrum and L. kederai from M. buchanani.